Penerapan Paradigma OOP dalam Pengembangan Sistem Penilaian Siswa Berbasis Web di SMK Negeri 1 Cepu - Muksan Junaidi; Indra Gunawan; Fitria Rizqi Nurdiana (Lembaga Pengembangan Kinerja Dosen, 2025)
The student grade processing system at SMK Negeri 1 Cepu has traditionally relied on manual handwritten records, which are time-consuming, prone to errors, and inefficient for long-term data management. This study aims to develop and implement a web-based student grading system using an object-oriented design approach to improve accuracy and efficiency. The system was developed using the System Development Life Cycle (SDLC) with the Waterfall model, employing PHP as the programming language and MySQL as the database. The development process includes requirement analysis, system design, coding, testing, and maintenance. The system utilizes primary data from the 2023/2024 academic year, covering 1,134 students, including user information, academic data, student grades, and grade reports. Black box testing results show 100% functionality compliance. The resulting application can be accessed via laptops and school computers, supporting school staff in managing, processing, and tracking student academic performance effectively each semester.